Prediksi Saham PT. Aneka Tambang Tbk. dengan K-Nearest Neighbors - Lathifah Alfat; Hendi Hermawan; Aviana Rustandiputri; Rizky Inzhagi; Refi Tandjilal (JSAI (Journal Scientific and Applied Informatics), 2022)
Information technology has spread continuously, that changes data into big data. That data can be saved, warehoused, and mined to get valuable information or knowledge. Data mining is a process of implementing a machine learning algorithm, to extract information from data. Prediction calculates information in the future from previous data. The investor needs to predict PT Aneka Tambang stocks so it may reduce the financial risk. This work models a prediction of PT Aneka Tambang stocks using the K-Nearest Neighbors algorithm. The resource of processed data is from open source from 2018 to 2021. Prediction results prove that the PT Aneka Tambang stock model is optimum in the composition of data training: testing about 9:1, with an accuration value approximately 93,36%.